A plasma chemistry model for H2/SiH4 mixtures used in PECVD processes. (1st May 2023) - Sushkov, Vladimir; Rachdi, Lazhar; Hofmann, Marc
Abstract: Plasma chemical processes in H2 /SiH4 discharges are critically reviewed. A model set of reactions is proposed which includes temperature and pressure-dependent reaction rates and describes Siy Hx (y ≤ 3) chemistry. Using a 2D fluid plasma simulator, the model has been tested under three different set of operating conditions. First, it has been validated against the experimental benchmark data (Horvath and Gallagher (2009) J. Appl. Phys. 105, 13304). Based on considerations of atomic hydrogen content, the branching of SiH4 dissociation channels and the H surface loss probability have been defined more accurately. Then, simulations have been also performed for the plasma source of a PECVD tool from Meyer Burger Germany. A very good agreement between the computed and experimentally determined deposition rates can be stated.